Peningkatan Produktivitas Cement mill melalui Pendekatan Overall Equipment Effectiveness dan Six Big Losses - Prasiska Dwiana Putri; Aswan Munang; Encep Jianul Hayat; Khikmatul Aliyah (Jurnal Kalibrasi, 2026)
PT XYZ faces a high downtime problem in Cement Mill Unit One, which has an impact on decreasing productivity and operational efficiency. This study aims to evaluate the effectiveness level of the machine using the Overall Equipment Effectiveness (OEE) method and to identify the root causes of the problems through Six Big Losses analysis and Fishbone Diagram. The results show that the average OEE value of Cement Mill Unit One in 2024 only reached 57 percent, which is still below the international ideal standard of 85 percent. This low effectiveness is dominated by idling and minor stoppages at 32.30 percent, followed by reduced speed losses at 23 percent, and equipment failure loss at 17.57 percent. Through the Fishbone Diagram analysis, the main causes of these losses were found to originate from human, machine, method, and environmental aspects. The proposed improvement recommendations include digitalizing maintenance documentation, implementing strict routine maintenance scheduling, improving operator competence, controlling the moisture content of input materials, and optimizing workplace cleanliness.